2021
DOI: 10.1001/jamanetworkopen.2021.28575
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance and Access Among Black and Latinx Communities

Abstract: IMPORTANCEBlack and Latinx communities have faced disproportionate harm from the COVID-19 pandemic. Increasing COVID-19 vaccine acceptance and access has the potential to mitigate mortality and morbidity from COVID-19 for all communities, including those most impacted by the pandemic. OBJECTIVE To investigate and understand factors associated with facilitating and obstructing COVID-19 vaccine access and acceptance among Black and Latinx communities. DESIGN, SETTING, AND PARTICIPANTS This community-partnered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
114
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 35 publications
12
114
0
2
Order By: Relevance
“…Community leaders, religious leaders, close family members, and friends were reported to be very influential in mobilizing communities for COVID-19 vaccination. This lends support to other studies that have found that perceived social norms are positively associated with people's intentions to get vaccinated, including vaccination with a COVID-19 vaccine, and the importance they give to getting vaccines [8,36,37]. As vaccines are made available to more and more people in these countries, it will be important that people see or hear that most people around them are planning to get a COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 80%
“…Community leaders, religious leaders, close family members, and friends were reported to be very influential in mobilizing communities for COVID-19 vaccination. This lends support to other studies that have found that perceived social norms are positively associated with people's intentions to get vaccinated, including vaccination with a COVID-19 vaccine, and the importance they give to getting vaccines [8,36,37]. As vaccines are made available to more and more people in these countries, it will be important that people see or hear that most people around them are planning to get a COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 80%
“…A recent review of published national surveys in the US identified several factors significantly associated with lower individual vaccine readiness among Latinx and Black/African American individuals, including socioeconomic status, medical mistrust, racial discrimination, exposure to misinformation and myths, and mistaken beliefs about vaccine efficacy and potential side effects [ 11 ]. Specifically, low vaccination readiness was attributed to those who were younger in age, have lower income and no college degree, have conversative political leanings, living in rural neighborhoods, living in multigenerational households, mistrust medical systems and have experienced racial discrimination [ 12 17 ]. Some surveys in the US have also found less vaccine confidence among Asian individuals relative to white respondents [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that U.S. Latino populations (and Black populations) report historical mistreatment in research (e.g., Tuskegee study) and feel as though their voice is ignored by medical professions, leading to mistrust in those developing and distributing the vaccine. 41 However, other research suggests health professionals, academic institutions, and government agencies were the most trusted sources of information about COVID-19 and were trusted more than news media, family/friends, and social media. 42 Although trust in sources sending information about the vaccine is important because of the influence it can have on intention to get vaccinated against COVID-19, 43 it is unknown how U.S. Latino populations perceive information sources reporting about COVID-19.…”
Section: Discussionmentioning
confidence: 99%